Effects of Ramadan on the diurnal variations of repeated-sprint performance - Aloui, A.; Chaouachi, A.; Chtourou, H.; Wong, D. P.; Haddad, M.; Chamari, K.; Souissi, N. (International Journal of Sports Physiology and Performance, 2013)
Purpose: This study examined the effects of Ramadan on cycling repeated-sprint ability (RSA) and corresponding diurnal variations. Methods: Twelve active men performed an RSA test (5 × 6-s maximal sprints interspersed with 24 s passive recovery) during morning and afternoon sessions 1 wk before Ramadan (BR), during the second (R2) and the fourth (R4) weeks of Ramadan, and 2 wk after Ramadan (AR). Maximal voluntary contraction was assessed before (MVCpre), immediately after (MVCpost), and 5 min after the RSA test (MVCpost5). Moreover, hematocrit, hemoglobin, and plasma sodium and potassium (K+) concentrations were measured at rest and after the RSA test and MVCpost. Results: Overall, peak power (Ppeak) during the RSA test decreased throughout the 5 sprints. Ppeak measured in the first sprint and MVCpre were lower during Ramadan than BR in the afternoon (P < .05) and higher in the afternoon than the morning BR and AR (P < .05). However, this diurnal rhythmicity was not found for the last 4 sprints` Ppeak, MVCpost, and MVCpost5 in all testing periods. Furthermore, the last 4 sprints` Ppeak, MVCpost, MVCpost5, and morning MVCpre were not affected by Ramadan. [K+] measured at rest and after the RSA test and MVCpost were higher during Ramadan than BR in the afternoon (P < .05) and higher in the afternoon than the morning during Ramadan (P < .05). Conclusions: Fatigability is higher in the afternoon during Ramadan, and, therefore, training and competition should be scheduled at the time of day when physical performance is less affected.